PERANCANGAN PROGRAM PENGELOLAAN DATA KEUANGAN PASIEN RAWAT JALAN BPJS PADA RUMAH SAKIT GRAHA JUANDA BEKASI - Redaksi Tim Jurnal (KILAT, 2018)
In today's era of globalization, information technology is speeding up. The computer is a device that was created to facilitate human work, while achieving good progress in the manufacture of hardware and software. Graha Juanda Hospital is a service business engaged in the field of health services. BPJS outpatient financial system that is done still manually from the calculation, data processing until the making of the report so it is possible at the time penginputan data error occurred in the recording or less accurate in the report made and delays in search data required. by using BPJS outpatient data management system that computerized BPJS outpatient financial data management will be more effective and efficient. In addition, the data stored neatly if at any time needed then the search data will be easier.